Cleft Lip and/or Cleft Palate: Prenatal Accuracy, Postnatal Course, and Long-Term Outcomes - Sivan Farladansky-Gershnabel; Hadar Gluska; Nufar Halevi; Neta Kotser; Maya Sharon-Weiner; Hanoch Schreiber; Rivka Sukenik-Halevi; Yaniv Ebner; Shmuel Arnon; Ofer Markovitch (MDPI AG, 2022)
Orofacial clefts include cleft lip (CL) and cleft palate (CP). This retrospective study assessed the efficacy of prenatal sonographic diagnosis of isolated and non-isolated cases of CL/CP and the postnatal outcomes of these children. Data regarding patients diagnosed and treated in the tertiary orofacial clinic from 2000 to 2020 were retrieved from electronic medical records and telephone-based questionnaires. Isolated CL was found in 7 cases (7.2%), isolated CP in 51 (53%), and combined CL/CP in 38 (39.5%), and 22 cases (23%) were associated with other anomalies. Among 96 cases, 39 (40.6%) were diagnosed prenatally. Isolated CL was diagnosed in 5/7 (71.5%), combined clefts in 29/38 (76.3%), and CP in 7/51 (13.8%). Prenatal chromosomal analysis performed in 32/39 (82%) cases was normal for all. The rate of surgical intervention in the first year of life was 36/38 (94.7%) for combined clefts, 5/7 (71.4%) for CL, and 20/51 (39%) for isolated CP. Most children had speech therapy (23/38 (60.5%), 3/7 (42.8%), and 41/51 (80.3%), respectively) and psychotherapy (6/38 (15.7%), 3/7 (42.8%) and, 15/51 (29.4%), respectively). The accuracy rate of sonographic prenatal diagnosis is low. Our results emphasize the suggested work-up of fetuses with CL and/or CP and improvements to parental counseling, as well as their understanding and compliance regarding post-natal therapeutic plans.